Penggunaan Pendekatan Saintifik Model Project Based Learning Metode Simulasi untuk Meningkatkan Minat dan Hasil Belajar Bahasa Inggris Pada Materi Label dan Recipe di Kelas IX 2 SMP N 1 Payakumbuh Semester Ganjil Tahun Pelajaran 2018-2019 - Yunia Irianti (Journal on Education, 2022)
The purpose of this study was to determine whether through a scientific approach the Project Based Learning model simulation method could increase interest and learning outcomes in English label and recipe material in class IX 2 SMP N 1 Payakumbuh Odd Semester 2018/2019 Academic Year. This research method is classroom action research. This research consists of four stages, namely planning, action, observation and reflection. which was carried out in two cycles at SMP N 1 Payakumbuh. The population in this study were students of class IX with the sample IX 2 and researchers. This research took place from the beginning of August 2018 to the end of November 2018. The instruments used were interest questionnaires, field notes and learning outcomes tests. Based on the results of the CAR assessment, information was obtained that the Project-based learning model was proven to increase students' interest and learning outcomes. From the data analysis, it can be seen that there is an increase in students' interest in learning from the pre-cycle to the first cycle by 30% and 7.2% from the first cycle to the second cycle. Value Learning outcomes in the form of knowledge, skills and attitudes also increased. The value of knowledge from pre-cycle to cycle I was 6.3% and from cycle I to cycle II was 2.4%. The skill value from pre-cycle to cycle I was 2.2% and from cycle I to cycle II was 2.1%. The average predicate attitude of students in the pre-cycle is B. After taking action in cycle I and cycle II, it increases to A.